Pengaruh Leverage, Gender Diversity, and Free Cash Flow Terhadap Kebijakan Dividen - Nurainun Bangun, Davin, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
This study aims to determine the effect of leverage, gender diversity, and free cash flow on dividend policy. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. The sampling method used was purposive sampling. Dividend policy is determined by the dividend payout ratio. The result of this study stated that the gender diversity didn’t have a significant effect on dividend policy, while leverage and free cash flow had a significant effect on dividend policy.